Kesetaraan Ayah dan Ibu dalam Perspektif Al-Qur'an - Andika, Erwin Saputra; Syafruddin, Syafruddin; Ashadi, Andri; Saputra, Edriagus (Ikhtisar: Jurnal Pengetahuan Islam, 2023)
Parents are people who are entitled to the glory and appreciation of their children. However, in terms of giving appreciation to both people, sometimes children make a difference between the two. A mother gets a higher award than her father, so here there is discrimination in the form of glorifying them. Therefore, this study aims to reveal the assessment of the Qur'an on the equality of fathers and mothers in Islam, so as not to bring up arguments that can corner one another. This research uses descriptive qualitative methods related to the equality of fathers and mothers in the perspective of the Qur'an. The results of this study can be concluded, that the Qur'an highly respects both parents and has the same rights and obligations of their children. This can be seen from the form of equality described in the Qur'anic verse which explains the division of inheritance, filial piety to both parents, wills, provision of a living, justice, principles in Islamic teachings, lessons for the former and disobedience to both people old.